Low-Level Laser Therapy (LLLT) on Soft Tissue Healing: A Case Report with Literature Review (Journal of Shaheed Suhrawardy Medical College, 2013)
Variety of skin wounds are difficult to treat. Cutaneous lesions are representing the dilemma due to high morbidity. To treat these lesions low-level laser therapy (LLLT) is currently available. Experimental in vitro and in vivo studies have been under development. LLLT is an effective method to modulate tissue repair. In this case report LLLT was applied to a women presenting with wound healing and the result was excellent.DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20770J Shaheed Suhrawardy Med Coll, 2013;5(2):117-121